Early Thailand from prehistory to Sukhothai - Higham, Charles; Rachanie Thosarat (River Books, 2012)
Dramatic new archaeological discoveries over the past ten years demand a new look at Thailand s past. Drawing on his previous work, Prehistoric Thailand, this book with over 40% new material, covers the history of the kingdom from the first human settlement.